Effect of S2Cl2 Addition on the Sulfate Attack of Hydrated Portland Cement - Yeprem, H. Ayguel; Goekmen, Selahattin (CARL HANSER VERLAG, 2009)
In this study the resistivity effect of laboratory-produced S2Cl2 as an additive in Portland cement PC 32.5 which was hydrated at the water/cement ratio of 0.5 and room temperature against sulfate attack in the curing solution of 0.35 M sodium sulfate was investigated. Hydrated cement products were determined by using X Ray Diffraction (XRD) and Thermogravimetry-Differential Thermal Analyses (TG-DTA) techniques. The additive substance, S2Cl2 in Portland cement, was used 5 and 10 percent by weight. The highest compressive strength value was found as 36.7 MPa in case of hydrated cement PC 32.5, samples containing 5 % S2Cl2 (additive) after curing time of 28 + 21 days.
Keywords: CONCRETE; Materials Science